Modernity's enchanting shadow: The Hall of Fantasy, horror programmes and US post-war radio. Issue 2 (1st November 2010) - Killmeier, Matthew A
This article offers a cultural history of the post-war horror radio anthology series The Hall of Fantasy (19471953). It unearths the particular significances of the series as a species of horror radio, and contributes to and refines our understanding of post-war radio. I argue that The Hall of Fantasy is formally innovative in its expressionistic use of the radio medium to heighten listeners' emotional involvement with the drama. And the series is culturally rich as it mines post-war modernity for thematic resources that resonate with audiences' anxieties. The Hall of Fantasy constructs a shadow of post-war modernity that suggests the cultural potency of enchantment.